2016
DOI: 10.1371/journal.pone.0152045
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Dominance Effects in the Multivariate GBLUP Model

Abstract: New proposals for models and applications of prediction processes with data on molecular markers may help reduce the financial costs of and identify superior genotypes in maize breeding programs. Studies evaluating Genomic Best Linear Unbiased Prediction (GBLUP) models including dominance effects have not been performed in the univariate and multivariate context in the data analysis of this crop. A single cross hybrid construction procedure was performed in this study using phenotypic data and actual molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…Studies using simulated datasets have suggested that multitrait models can be used to increase predictive ability for low-heritability traits that are correlated with higherheritability traits, or when a trait is simply too difficult or expensive to measure in all individuals within a population (Calus and Veerkamp, 2011;Jia and Jannink, 2012;Hayashi and Iwata, 2013;Guo et al, 2014). Several studies have subsequently assessed multitrait GS in datasets consisting of nonsimulated phenotypic data (Jia and Jannink, 2012;Pszczola et al, 2013;dos Santos et al, 2016;Rutkoski et al, 2016;Schulthess et al, 2016;Wang et al, 2016).…”
mentioning
confidence: 99%
“…Studies using simulated datasets have suggested that multitrait models can be used to increase predictive ability for low-heritability traits that are correlated with higherheritability traits, or when a trait is simply too difficult or expensive to measure in all individuals within a population (Calus and Veerkamp, 2011;Jia and Jannink, 2012;Hayashi and Iwata, 2013;Guo et al, 2014). Several studies have subsequently assessed multitrait GS in datasets consisting of nonsimulated phenotypic data (Jia and Jannink, 2012;Pszczola et al, 2013;dos Santos et al, 2016;Rutkoski et al, 2016;Schulthess et al, 2016;Wang et al, 2016).…”
mentioning
confidence: 99%
“…For comparison to the three Bayesian models, we also evaluated two different formulations of the multivariate GBLUP model (Henderson and Quaas 1976; dos Santos et al 2016b; Fernandes et al 2018) that recovered information between traits and/or time points. In the first formulation, only PH measurements across time points were used (MTi-GBLUP).…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of GP studies conducted in crop species have only tested models for predicting individual traits. However, recent studies have shown the advantages of combining multiple correlated traits in a GP model (Calus and Veerkamp 2011; Jia and Jannink 2012; Fernandes et al 2018), allowing genetic correlations among secondary traits to be leveraged for improving predictions of a target trait (dos Santos et al 2016b; Okeke et al 2017). Most of these efforts used multi-trait GBLUP—a type of multivariate mixed linear model that incorporates a genomic relationship matrix (Gianola et al 2015).…”
mentioning
confidence: 99%
“…Models assuming dominance and epistatic effects have been proposed (Su et al, 2012;Vitezica et al, 2013;dos Santos et al, 2016) but are still rarely used in plant breeding, despite strong evidence that these models are important in understanding the genetic architecture of quantitative traits (Carlborg and Haley, 2004). As mentioned above, all these genetic models vary with the addition or removal of genetic effects or in the form of relatedness estimations between individuals of a current population, which have shown relationships relative to a reference population (Zeng et al, 2005;Van Raden, 2008;Powell et al, 2010;de Los Campos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%